ANALISIS WACANA VAN DIJK TENTANG REALITAS BEDA AGAMA PADA FILM CIN(T)A - Munanjar, A. (Universitas Bina Sarana Informatika, 2016)
This article focuses on love reality on different religion. The illustrated reality in a Cin(T)a film’s script attract various interpretation. The different interpretation arises when each audience construct the reality differently for every visualization through movie scene. This difference becomes the reason why analyzing love reality interpretation at Cin(T)a movie. This research uses qualitative method with van dijk discourse analysis study. This research covers the language used in the text or movie’s script. The research goal is to understand act and context as background, situation, event, and condition. Those acts can represent some meaning, opinion, and ideology. Movie’s director uses narrative and cinematic approach to sharpened reality construction of love from different religion. This research finds that Cin(T)a was constructed through ideology based on God’s concept. The meaning founded in Cin(T)a movie is the intimate of people and his/ her God. This relationship build God’s approach as life’s guideline.Keywords: Reality construction, movie, ideology, narrative-cinematic